Effect and mechanism of HMG-CoA reductase inhibitor on the improvement of elderly essential hypertension-induced vascular endothelial function impairment based on the JAK/STAT pathway - Wen Yuan; Hongjun Fan; Haibing Yang; Liang Tang; Zhiming Liu; Fan Ouyang; Wei Luo; Yong Yan (BMC, 2023)
Abstract Objective Our research was designed to figure out the influence and mechanism of 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase inhibitor on the improvement of elderly essential hypertension-induced vascular endothelial function impairment based on the JAK/STAT pathway. Methods Eighty-six elderly patients with essential hypertension were randomized into a control group (oral Amlodipine Besylate Tablets) and an observation group (oral Amlodipine Besylate Tablets + HMG-CoA reductase inhibitor atorvastatin calcium). Patients in both groups were treated with the drug for 12 weeks. Blood pressure, serum levels of inflammatory factors, and vascular endothelial function indicators, and levels of blood lipids were measured. The modeled rats were treated with atorvastatin calcium and a JAK/STAT pathway inhibitor (AG490), and the levels of cardiac function-related indices, left ventricular mass index, lipid levels, serum inflammatory factors and vascular endothelial function-related indices were detected in each group. Results HMG-CoA reductase inhibitor improved blood pressure levels, lipid levels, serum inflammatory factor levels and cardiac function in elderly patients with essential hypertension. Both HMG-CoA reductase inhibitor and AG490 improved blood pressure levels, lipid levels, serum inflammatory factor levels and cardiac function in SHR rats. Both HMG-CoA reductase inhibitor and AG490 decreased p-JAK2/JAK2 and p-STAT3/STAT3 expression levels. Conclusion Our study demonstrates that HMG-CoA reductase inhibitor improves elderly essential hypertension-induced vascular endothelial function impairment by blocking the JAK/STAT pathway.